2017
DOI: 10.1177/1538192717701252
|View full text |Cite
|
Sign up to set email alerts
|

Latina/o Transfer Students’ Selective Integration and Spatial Awareness of University Spaces

Abstract: Using the framework of physical campus ecology and socio-academic integration moments theory, the researcher sought to identify physical university spaces that successful Latina/o transfer students turned to as sites of positive socio-academic integration. Findings revealed that students developed a keen spatial awareness of comfort spaces where they selectively engaged in moments of socio-academic, nonsocial, and nonacademic integration. This study is important to understand students' perceptions about educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…I interviewed students within the first 2 weeks after Trump's victory to understand their visceral and immediate reactions given that students' emotional responses were heightened due to the psychologically intense nature of the election (Adames, 2016). Phone interviews are conducive to studies with students who may be weary of research studies (Andrade, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I interviewed students within the first 2 weeks after Trump's victory to understand their visceral and immediate reactions given that students' emotional responses were heightened due to the psychologically intense nature of the election (Adames, 2016). Phone interviews are conducive to studies with students who may be weary of research studies (Andrade, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The interview protocol was composed of two parts. The first part used a short demographics survey that previous studies used (Andrade, 2017), which asks students to self-identify their gender, age, nationality, and ethnicity. The second part included questions related to the election, including:…”
Section: Instrumentmentioning
confidence: 99%
“…Research Question 2: What kinds of positive validation or services did administrators and educators provide to help the students throughout the year? Method I used one-on-one qualitative interviews in the present study, which researchers use in educational settings to understand the holistic profiles, relationships, and perceptions of students (Andrade, 2018;Creswell, 2013;Marshall & Rossman, 2011) and are fitting when studying the experiences of undocumented students (Anguiano & Nájera, 2015). In addition, the present study is an example of a longitudinal qualitative study.…”
Section: Validation Theorymentioning
confidence: 99%
“…I conducted one-time, face-to-face and phone interviews, which are appropriate given the busy schedules of undocumented students (Andrade, 2017(Andrade, , 2018. On average, the interviews lasted between 45 and 60 min.…”
Section: Recruitment and Proceduresmentioning
confidence: 99%
“…Research has found that for racially/ethnically minoritized students, campus artifacts are particularly important for social integration, racial/ethnic identity development, and a sense of belonging (Andrade, 2018;Lozano, 2010;Patton, 2006). Most research on campus artifacts has focused on racially/ethnically minoritized students' perspectives at PWIs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%